Structural Design and Motion Analysis of Reconfigurable Tracked Pipeline Robot - Jia Chaoyu,; Wan Zakaria, Wan Nurshazwani; Chen Pengwei,; Mohd Nor Azmi Bin Ab Patar, (International Journal of Integrated Engineering, 2024)
There has been a renewed interest in development of pipeline robot to meet the demand of regular inspection and maintenance. This paper focuses on structural design and motion analysis of the developed reconfigurable tracked pipeline robot. The robot features an active diameter-changing mechanism, and an independent control drive module allowing it to adjust its tracks to fit the inner wall size of circular pipelines during manoeuvring. A comprehensive dynamic motion analysis was conducted to determine the necessary motion and force for effective robot movement. Both simulation and experimental tests were performed in horizontal and sloping pipelines. It was found that the angular velocity is relatively stable and reciprocating within a range of -2.7 to 1.7 °/s. The simulation results exhibit that the robot has good adaptability to pipeline sizes which demonstrate that the robot performs effectively within circular pipelines.